FACTORS ASSOCIATED WITH THE USE OF IUD CONTRACEPTION IN SIMARMATA VILLAGE, SUB-DISTRICT SIMANINDO DISTRICT SAMOSIR DISTRICT IN 2023 - Sinurat, Astriatalita Lastiar (Akupun Tour Publisher, 2023)
Background: Contraception is avoiding/preventing pregnancy as a result of a meeting between an egg and a sperm cell. Based on the purpose and objectives of contraception, those who need contraception are couples who are actively having sex and both have normal fertility but do not want pregnancy.Based on the initial survey in Simarmata Village, it turns out that IUD family planning users are still small compared to pills, injections and others. In 2021 there were 103 PUS, the number of family planning participants was 69 and IUD participants were 13 people while in 2022 there were 103 PUS, the number of family planning participants was 73 and IUD participants were 13 people. Purpose: The purpose of the study was to determine what factors were associated with the use of IUD contraception in Simarmata Village, Simanindo District, Samosir Regency in 2023. Method: This study was conducted from December 2022-August 2023 in Simarmata Village Simanindo District Samosir Regency. The population in this study were all mothers who use contraception in Simarmata Village Simanindo District Samosir Regency as many as 73 people in 2022. Univariate analysis is an analysis used to explain the characteristics of each variable to be studied. Bivariate analysis is used to test the hypothesis and the statistical test used is the Chi-Square test ( ) at a significance level of 95% (0.05). Results: The results of statistical tests on chi-square analysis obtained variable number of children p-value of 0.03 <0.05 means there is a relationship between the number of children with the use of IUD contraceptives, knowledge obtained p-value of 0.000 <0.05 means there is a relationship of knowledge with the use of IUD contraceptives and variable husband support obtained p-value of 0.000 <0.05 means there is a relationship of husband support with the use of IUD contraceptives in Simarmata Village Simanindo District Samosir Regency Year 2023. Disscusion and Conclusion: For this reason, it is advisable for PUS women to ask for support from their husbands in the use of IUD contraceptives. PUS also need to increase knowledge by exploring information and limiting the number of births of their children.